PENGARUH TRANSFORMASI DIGITAL DAN INTEGRITAS TERHADAP KINERJA PEGAWAI KEJAKSAAN TINGGI LAMPUNG - Christiyandi, Dwitya Rizky; Khairudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Optimal employee performance is a key factor in supporting the effectiveness of task implementation and the quality of legal services within law enforcement institutions; however, employee performance at the Lampung High Prosecutor’s Office has not yet reached an optimal level. This study aims to analyze the effect of digital transformation and integrity on employee performance at the Lampung High Prosecutor’s Office. The research employed an explanatory quantitative approach using a survey of 175 respondents. Data were analyzed using the Statistical Package for the Social Sciences (SPSS). The results indicate that digital transformation has a negative and significant effect on employee performance, reflecting that the implementation of existing digital systems and technologies has not been able to optimally enhance employee performance. This condition indicates the presence of constraints related to adaptation, digital literacy, and consistency in the use of electronic systems, which may potentially reduce work effectiveness. Furthermore, integrity has a positive and significant effect on employee performance, indicating that values such as honesty, responsibility, and compliance with regulations play an important role in improving employee performance. In addition, the simultaneous test results show that digital transformation and integrity have a significant effect on employee performance, indicating that employee performance is influenced by the integration of digital system implementation and the strengthening of integrity values.